Islamic Value-Based Principal Leadership in Improving Teacher Professionalism at Salman Al Farisi Integrated Islamic Elementary School and Al Khairiyah Integrated Islamic Elementary School (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyse the implementation of principal leadership, problems faced by principals, and the principal's efforts in overcoming problems at Salman Al Farisi Integrated Islamic Elementary School and Al Khairiyah Integrated Islamic Elementary School. This study was conducted using a qualitative descriptive approach at Salman Al Farisi Integrated Islamic Elementary School and Al Khairiyah Integrated Islamic Elementary School. The study subjects included principals, vice principals for curriculum, and teachers. Data were collected through interviews, observations, and documentation. To ensure credibility and validity, triangulation techniques were applied. Data were analysed using the interactive model developed by Miles, Huberman, and Saldana. The results show that the implementation of principal leadership at Salman Al Farisi Integrated Islamic Elementary School and Al Khairiyah Integrated Islamic Elementary School is grounded in Islamic values such as trustworthiness, exemplary conduct, justice, deliberation, and compassion. The principal functions not only as a manager but also as a spiritual mentor, promoting Islamic professionalism among teachers. Challenges include inconsistent teacher discipline, limited facilities, and administrative demands. To address these issues, principals conduct intensive coaching, reinforce an Islamic work culture, collaborate with foundations and parents, and implement continuous evaluation based on Islamic principles.